PROJECT-BASED LEARNING IN THE TEACHING OF WRITING IN HIGHER EDUCATION CONTEXTS IN INDONESIA: Searching for Best Practice - Irpan Apandi Batubara, - (2024)
Project-Based Learning (PjBL) has been strongly recommended as one of the approaches to teaching, including the teaching of English in Indonesian contexts at all levels of education. However, despite being stated in the Indonesian educational policy as a recommended approach, PjBL has been implemented in diverse ways and interpretations to meet the policy requirement without following references to its best practices. This study aimed to explore how PjBL is recontextualized in teaching writing in the Indonesian higher education context to search for its best practices. The study followed a qualitative multi-case study involving three lecturers who have been applying PjBL in the classrooms as participants. This study gathered data from classroom observations, interviews, and focus group discussions. The data analysis was conducted by qualitatively condensing and coding the raw data into thematic classification. The meaningful data were coded with references to the theory of PjBL in language teaching including stages and key features. The findings show that PjBL has been recontextualized in the teaching of writing to meet contexts of learners, yielding a potential model of PjBL in practice in a higher educational context. Case 1, Case 2, and Case 3 show some characteristics in stages, organizing meetings, topics, publications, and reflections featuring specific characteristics of the lecturers' decision in recontextualizing PjBL. The stages of writing in PjBL including outlining, draft writing, reviewing, revising, editing, and publishing. Furthermore this study indicates the support of PjBL on collaborative writing. Some challenges encountered by the lecturers in implementing PjBL were mostly related to having students engage in learning. In conclusion, the best practices in this study constitutes a combination of PjBL with genre-based teaching and writing process approach. Key words: Recontextualizing, PjBL, Teaching of Writing, Higher Education